Pengaruh Green Marketing Mix Terhadap Keputusan Pembelian Konsumen pada Produk Ramah Lingkungan (Mulia Pratama, 2022)
This review article aims to explore the relationship between green marketing mix and purchase intention of consumers. Green marketing mix refers to the set of strategies and tactics that a firm adopts to promote its products or services as environmentally friendly and socially responsible. Purchase intention is the likelihood that a consumer will buy a product or service in the future. The article synthesizes the existing literature on the topic and identifies the main factors that influence the green marketing mix and purchase intention. It also discusses the implications and challenges for managers and researchers in this field.